Phenotypic and molecular characterization of Rhizobium vitis strains from vineyards in Turkey - CANIK OREL, Didem; KARAGOZ, Alper; DURMAZ, Rıza; ERTUNC, Filiz (Phytopathologia Mediterranea, 2016)
Crown gall-affected grapevine samples were collected during 2009–2010 from major vineyards, located in different Turkish provinces. One hundred and three bacterial strains were obtained from 88 vineyards and 18 grapevine varieties; they were tumorigenic when inoculated in tobacco, sunflower and Datura stramonium plants and were identified as Rhizobium vitis using biochemical and physiological tests as well as PCR and specific primers. Nineteen R. vitis strains presented a number of anomalous biochemical and physiological characters. PCR and opine-specific primers revealed the presence of octopine/cucumopine-type plasmid in 82 R. vitis strains, nopaline-type plasmids in 18 strains and vitopine-type plasmids in three strains. Clonal relationship of strains was determined using Pulsed Field Gel Electrophoresis following digestion of genomic DNA with the restriction endonuclease PmeI. The greatest genetic diversity was found for the strains from Denizli, Ankara and Nevşehir provinces. Nopaline and vitopine-types of Rhizobium vitis were detected for the first time in Turkey.